PENINGKATAN KEMAPUAN BERPIKIR KRITIS MAHASISWA PIAUD PADA MATA KULIAH NEUROSAINS DENGAN METODE PEMBELAJARAN ACCELERATED LEARNING - Agung Kaisar Siregar (BUHUTS AL-ATHFAL: Jurnal Pendidikan dan Anak Usia Dini, 2022)
This research is a quantitative research with a quasi-experimental approach. This research is used because through this research it is expected to cause a situation or change aimed at seeing a result of a treatment. The population is all PIAUD students majoring in UIN Sheikh Ali Hasan Ahmad Addary Padangsidimpuan, and the subjects are PIAUD students in semester 4, because this semester is offered courses neuroscience course. So the sample was not chosen at random, but was accepted as the condition was due to the limited class in this fourth semester. The purpose of this research is to see the improvement of students' critical thinking skills after carrying out Accelerated Learning (AL) learning, using test questions with critical thinking indicators as a data collection technique. The increase in students' critical thinking skills according to the criteria for increasing n-gain shows that the increase in students' critical thinking skills is classified as high.